Micromorphology of trichomes and composition of essential oil of Teucrium capitatum - Antunes, Teresa (2004)
The morphology and distribution of the glandular trichomes of Teucrium capitatum L., as well as the chemical composition of the essential oils, were studied. Important differences were found with regard to the major constituents of the essential oils of five populations of T. capitatum grown in Portugal. The oil isolated from one population was characterized by a high content of oxygenated monoterpenes (33.0%), isomenthone (7.7%) being the major constituent. Another oil from a population collected from the same region was dominated by monoterpene and sesquiterpene hydrocarbons (43.9% and 23.2%, respectively), alpha-pinene (7.7%), sabinene (11.2%) and beta-pinene (10.3%) being the main compounds. The oils from the other three populations were characterized by a high content of both sesquiterpene hydrocarbons (23.0%, 32.2% and 33.2%) and oxygenated sesquiterpenes (39.7%, 23.4% and 20.4%). T-cadinol (24.1%) and alpha-cadinol (9.8%) were the major compounds in the oil from one population, whereas delta-cadinene (7.5% and 9.8%) and E-caryophyllene (5.4%) or alpha-muurolol (6.0%) were the major constituents in the other samples. The indumentum of the vegetative and reproductive ograns from the five populations of T. capitatum, observed under scanning electron microscopy, showed the same type and distribution of glandular and non-glandular trichomes. Since the ecological and edaphic features of the collecting sites were quite similar, the chemical polymorphism observed seems to be due to genetic factors. Copyright © 2004 John Wiley & Sons, Ltd.